Blastic plasmacytoid dendritic cell neoplasm: a report of four cases and review of the literature. (27th March 2012) - Borchiellini, D.; Ghibaudo, N.; Mounier, N.; Del Giudice, P.; Quinsat, D.; Ticchioni, M.; Perrin, C.; Cardot Leccia, N.; Lacour, J.P.
Abstract: Background  Blastic plasmacytoid dendritic cell neoplasm (BPDCN), formerly known as agranular CD4 + /CD56 + haematodermic neoplasm (CD4/CD56 HN), is a rare distinct form of lymphoma‐like entity known of dermatologists because of its marked predilection for cutaneous involvement, and its aggressive behaviour. Moreover, the association or the evolution to an acute leukaemia entity that still expresses CD4 and CD56 markers is almost systematic. This new described entity of 'CD4 + /CD56 + leukaemia' or 'leukaemia of plasmacytoid dendritic cell lineage' has a poor prognostic and may lead to include haematopoietic stem cell transplantation in the treatment strategy as early as possible. Report of cases  We report here four cases presenting with skin lesions and haematological signs. One of the patients underwent allogeneic stem cell transplantation, with a relapse‐free survival of 40 months. We discuss the diagnosis features as well as the treatment options. Conclusion  A collaborative work between dermatologists and onco‐haematologists is essential to give patients the best chance of complete and long‐term response.